Integrative Metabolomic and Microbiomic Profiling in Precision Pathological Diagnostics - Jassim, Noor Ahmed Hussein; Abboud, Dina Shihab Ahmed; Alwan, Jafar Falah Naeem; Baqi, Mohammed Muslim Hamdi; Hussein, Habib Mardan Mansi Abdul (American Journal of Biomedicine and Pharmacy, 2025)
The gut microbiome is a complex and diverse ecosystem of billions of microorganisms that maintains host health. In recent years, it has been understood that the gut microbiome affects metabolism, immunity, and the pathogenesis of a variety of human diseases. Metabolomics is a rapidly developing science that identifies and quantifies small molecules (below 1,000 Da) from all metabolic pathways in a biological system and studies their dynamics in space and time under different physiological conditions, genetic backgrounds, environmental exposures, and disease states. Metabolomics provides knowledge of the nature, concentration, and attachment sites of metabolites, as well as their molecular mechanisms of actions in multicellular systems. Given the vast and diverse microbial ecosystem, the metabolic products from communities were named as community (or environmental) metabolome, and the mining of community metabolites released by microbiomes was termed as community (or environmental) metabolomics. With new metabolomics pipelines recently developed, a variety of untargeted and targeted methods have been applied to analyze community metabolic products. Metabolomics can help identify the metabolites produced by the microbiome under different gut environmental conditions as well as those that are affected or changed due to the disease status; therefore, metabolites are promising candidates as biomarkers for clinical diagnosis. Precision medicine emerged as a concept to provide tailored health management for individuals. One main tenet of precision medicine is the identification of biomarkers that can stratify patients into subgroups likely to respond differently to therapeutic interventions. In addition to host genomes, it is suggested that gut microbiomes could serve as one of the most promising sources of biomarkers for precision medicine. Considerable efforts have been made to seek potential gut microbiome markers for chronic diseases.